2003
DOI: 10.1023/a:1023283628454
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was designed to isolate new genes related to apoptosis in rat pheochromocytoma (PC12) cells treated with hydrogen peroxide (H2O2), and to characterize the roles of the genes using both in vitro and in vivo models of oxidative injury. cDNA libraries were prepared from H2O2-treated and -untreated PC12 cells, and a ribosomal protein S9 (RPS9) clone was isolated by a differential screening method. Increase of RPS9 expression in both H2O2-treated PC12 and neuroblastoma (Neuro-2A) cells was shown by North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our research found that after OGD/R, the hypermethylated transcript functions were mainly enriched in pathological processes, including Huntington's disease and intrinsic apoptotic signaling pathways, whereas the hypomethylated transcript functions were mainly enriched in physiological processes. Moreover, the hub genes RPS9 and RPL8 of PPI network analysis were significantly increased in the brain tissue after cerebral ischemia and hemorrhage (Kim et al, 2003;Chen et al, 2019a). These findings indicate that m 5 C modification may also be involved in the pathological processes of cerebral injury.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our research found that after OGD/R, the hypermethylated transcript functions were mainly enriched in pathological processes, including Huntington's disease and intrinsic apoptotic signaling pathways, whereas the hypomethylated transcript functions were mainly enriched in physiological processes. Moreover, the hub genes RPS9 and RPL8 of PPI network analysis were significantly increased in the brain tissue after cerebral ischemia and hemorrhage (Kim et al, 2003;Chen et al, 2019a). These findings indicate that m 5 C modification may also be involved in the pathological processes of cerebral injury.…”
Section: Discussionmentioning
confidence: 73%
“…Heat shock protein family A (Hsp70) member 8 (HSPA8) played an important role in the occurrence and development of neurological diseases, such as Alzheimer's disease and Parkinson's disease (Lauterbach, 2013;Silva et al, 2014). Ribosomal protein L8 (RPL8) expression levels were significantly increased in the brain tissue after cerebral hemorrhage, and Ribosomal protein S9 (RPS9)expression was increased significantly in the neurons of the dentate gyrus after acute cerebral ischemia (Kim et al, 2003;Chen et al, 2019a). By analyzing the functions of the main gene modules through MCODE, we found that the main methylation gene modules were significantly related to basic life activities of cells, including gene expression, biosynthetic processes, energy metabolism and transport (Figure 5F), and these results were similar to previous studies (Yang et al, 2019).…”
Section: Functional Analysis Of Differentially Methylated M 5 C-modified Genes Between the Control And Ogd/r Groupsmentioning
confidence: 99%
“…ALDH18A1 is a protein implicated in proline and ornithine biosynthesis, and its expression is responsible for cellular ROS downregulation [61]. RPS9 is implicated in ribosomal biogenesis, has a protective role in the apoptotic process and exerts a protective mechanism against oxidative injury [62]. Interestingly, these proteins are all involved in protection against oxidative stress.…”
Section: Resultsmentioning
confidence: 99%